Aspek Hukum Rupiah Digital Dalam Transaksi Jual Beli Tanah - Kaharap, Nadiya Galang; Suwadi, Pujiyono; Setiyawan, Anang (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2024)
Digital currency as a transaction medium with the idea of introducing a decentralised currency. The absence of government intervention indirectly can potentially replace the unit of value of legal tender in a country. Efforts were made to anticipate this, and Bank Indonesia developed the Central Bank Digital Currency (CBDC) or digital rupiah as stipulated in Law Number 4 of 2023 concerning The Development and Strengthening of The Finansial Sector. The provision does not explicitly regulate security for digital rupiah users. The research aims to analyse the legal aspects of using digital rupiah as a transaction tool for land sale and purchase payments. The research method used is normative legal research with a statutory and conceptual approach. The development of the digital rupiah is inseparable from various risks, plus the absence of adequate regulations so that digital rupiah cannot be used in land sale and purchase transactions.